Cholecystocolic Fistula: A Diagnostic Dilemma (Bangladesh Journal of Medical Science, 2014)
Cholecystocolic fistula is a rare biliary-enteric fistula with a variable clinical presentation. Despite modern diagnostic tools a high degree of suspicion is required to diagnose it preoperatively1,2. Biliary-enteric fistulae have been found in 0.9% of patients undergoing biliary tract surgery. The most common site of communication of the fistula is a cholecystoduodenal (70%), followed by cholecystocolic (10-20%), and the least common is the cholecystogastric fistula accounting for the remainder of the cases. Even a case of choledochocolonic fistula through a cystic duct remnant has been reported3. These fistulae are treated by open as well as laparoscopic surgery with no difference in intraoperative and postoperative complications. We report a case of obstructive jaundice, which was relieved by itself and was investigated with abdominal ultrasonography and routine investigations but none of these gave us any clue to the presence of the fistula which was discovered incidentally during an open surgery and was appropriately treated. DOI: http://dx.doi.org/10.3329/bjms.v13i3.19156 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.329-331